Clinical Use of Pregabalin in General Practice in Catalonia, Spain: A Population-Based Cross-Sectional Study - Viñas-Bastart, Montserrat; Oms-Arias, Míriam; Pedraza-Gutiérrez, Àfrica; Lizano-Díez, Irene; Modamio, Pilar; Mariño, Eduardo L (Pain medicine (Malden, Mass.), 2018)
Abstract Objective The aim of this study was to determine the pattern of use of pregabalin and the appropriateness of treatment, so that interventions could be designed to improve various clinical approaches to the use of pregabalin to include unlicensed indications. Design A descriptive, cross-sectional, multicenter study was performed between April 2014 and January 2015. Setting Fifty-three primary health care centers covering 1,250,000 inhabitants. Subjects A total of 10,155 patients with pregabalin prescriptions. Methods Demographic (gender, age) and clinical (licensed indications for pregabalin, treatment duration, dosing schedule, diagnoses, kidney function, previous treatment with pregabalin, and additional drug treatment combined with pregabalin) variables obtained from health records were studied. The indicators were related to the daily dose of pregabalin, diagnoses, and treatment. Results A total of 64.2% of patients treated with pregabalin were female (mean age = 62.3 years; SD = 15.2 years). Twenty-nine patients were younger than age 18 years. A total of 68.2% of patients were taking pregabalin for an appropriate indication, 45.2% were using pregabalin off-label for bone and joint pain, and 15.1% were using pregabalin for fibromyalgia. A total of 71.9% of patients started treatment with pregabalin without previously using firstline drugs, such as amitriptyline or gabapentin, and 66% of active treatments had been initiated during the year before the study. In 47% of patients with glomerular filtration rates lower than 15 mL/min, the dose exceeded the maximum. Conclusions Our study reveals that pregabalin is used for unlicensed indications and often when firstline drugs have not been trialed and suggests that better routines in diagnosis and prescription may improve treatment outcomes. Our study also provides novel information about the use of doses of pregabalin that are higher than recommended for patients with renal impairment.